Analysis of energy production for local biomass resources in Perak Tengah - Syed Yusof, Syed Nazrin (Universiti Teknologi PETRONAS, 2016)
Energy production from local biomass resources has been given several attention as the fossil fuels has reached its maximum production. The main objectives are to analyze starch and sugar content for selected biomass resources from the Perak Tengah, to determine best pretreatment method viable for highest biofuel generation and to develop process flowsheet for the production of biofuel from biomass. There are 3 major method involved in converting the biomass to biofuel which is drying, hydrolysis and fermentation. The drying is separated into 2 types of drying which are air-drying and oven-drying. Hydrolysis used is the acid hydrolysis by using dilute acid sulphuric acid. The fermentation will be carried out by using yeast (Saccharomyces cerevisiae). The expected results from the conversion of biomass to biofuel is displayed in the form of efficiency of fermentation. Based on the three different parts of different trees, the highest fermentation efficiency is the oil palm leaves which is 56 %, followed by banana stem which is 50.8 % and lastly ‘lalang’ by 25.7 %